STUDY OF THE ACCURACY OF IMPROVED METHODS OF CALCULATING THE TIGHTNESS PARAMETERS OF OIL-FREE PISTON SEALS - TYMOSHCHUK, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Abstract - Based on the theory of stochastic fields, methods were developed for calculating the tightness parameters of oil-free piston seals for the performance of engineering calculation methods intended for the field of mechanical engineering. The purpose of the work is to analyze the accuracy of improved methods for calculating the tightness parameters of oil-free piston seals. The result is the creation of engineering methods for calculating tightness in oil-free cylinder-piston metal-polymer seals. The article considers the elastic contact of a highly anisotropic rough surface (polymer surface) with a smooth (metal surface). The task consists in the development and research of engineering methods for calculating the main characteristics of the tightness of oil-free cylinder-piston seals - the density of the inflow channels and the equivalent diameter of the channels in the conjugation zone of metal-polymer seals, as well as to perform an accuracy analysis of the developed methods. The dependence of the density of inflow channels on the complex of contact conditions is extreme. The channel density (the number of channels per unit of nominal profile length, fixed transversely to the direction of the flow of the medium) can be calculated as the difference between the surface of the contacting contact surfaces and the density of the depressions. that exceed a given level. The gas flow regime in the seal is determined by the Knudsen criterion. Based on the formula of the effective level of deformation for a given value of the complex of contact conditions of piston seals, the relationship between the density of the inflow channel and the complex of contact conditions was established using the developed Kanal program. As the contact conditions increase, the channel density first increases and then decre621.81ases. This is due to the influence of the process of combining contact spots during the loading process. The maximum number of channels is reached at K = 0.6315. An exact formula is derived to determine the channel density. Based on the exact formula, the calculation formula is obtained. The values calculated by the formula of exact and calculated channel density differ by no more than 0.0045. Exact formulas of equivalent diameters are derived. The dependence of equivalent diameters on the set of contact conditions was investigated. Calculation formulas of equivalent diameters are obtained on the basis of exact formulas. The values calculated by the exact and calculated formulas of the combined equivalent diameter differ by no more than 9%, for the combined equivalent diameter the difference does not exceed 10%.